Advancing Agro-Based Research - New Sunday Times, Noor Aswad (2008)
Taking the next sums up Universiti Putra Malaysia (UPM) approach to research. The university now aims to create an environment that inspires innovative research following its selection as a research university by the Higher Education Ministry in November 2006.